Natural ethics and informed consent Ética natural e consentimento livre e esclarecido - Hinshelwood, Robert (Universidade Estadual de Campinas, 2010)
In this paper I examine one way in which psychoanalysis could contribute a natural ethics based on the inherent psychological development of a moral conscience. Psychoanalytic object-relations theories postulate the fundamental relational nature of human beings, and therefore the correlated concerns about the well-being of others. The notion of unconscious projective identification central to some theories provides an ethic of integration.